Effect Of The Actıvatıon Force On The Healıng Level Of Asphalt Mıxture Wıth Embedded Capsules - Yalcin, Erkut; Yilmaz, Mehmet; Yalcin, Beyza Furtana (Avestia Publishing, 2024)
By increasing the asphalt mixtures' inherent capacity for self-healing, encapsulated rejuvenators can extend the service lives of asphalt pavements. The capsules are shattered when crack damage occurs, allowing the rejuvenator ingredient to seep into the cracks. In this work, a brand-new kind of capsule was created. Sunflower oil was a rejuvenator in these capsules. We looked at how well asphalt mixture samples with and without capsules self-healed under static loading. The capacity for self-healing of asphalt mixtures incorporating a novel class of capsules that contain sunflower oil as a rejuvenating agent. For this reason, the ability of the rejuvenating ingredient to diffuse inside of samples of virgin bitumen and the healing potential of combinations of cracked asphalt containing capsules have both been assessed. Due to the mechanical properties of the polymeric capsules examined. Then, using a unique mechanical test, the impact of capsule content on the crack-healing characteristics of asphalt mixtures was assessed at various healing durations (from 5 to 216h) and loads (from 0 to 85kN). As the applied load increases, the healing levels of the asphalt samples with capsules rise; later, the healing levels of the asphalt samples with capsule remain constant. According to the findings, the maximal healing level was typically attained after 96 hours and remained constant until 216 hours. © 2024, World Congress on Civil, Structural, and Environmental Engineering. All rights reserved.
9th World Congress on Civil, Structural, and Environmental Engineering, CSEE 2024 -- 14 April 2024 through 16 April 2024 -- London -- 312559
Keywords: Asphalt; Capsules; Self-healing; Sunflower oil